Legal Protection Against the Use of Brand Names for Geographical Indications on Trusmi Cirebon Batik - Saefullah, Faiz; Kharisma, Icah; Riana Sari, Usri; Hidayat, Dudung; Ismayana (Jurnal Legisci, 2024)
The importance of conducting this research is because there is an allegation of violation of the law against the object of Geographical Indication registered as a brand name by an entrepreneur using the name "Batik Trusmi" because it contains things related to geographical indications such as the place of origin of goods, production area, type of goods and character owned by a place. The purpose and purpose of this study is to research an alleged violation in the naming of a registered trademark because it uses a name that is identical to a geographical indication with logical legal reasons and grounds based on a legal perspective, analyzing the certainty of legal protection for the name "Batik trusmi" which is used as a trademark through legal discovery based on the perspective of existing legal regulations, and provides important information to see the facts through the legal science possessed by the author. The method used in this study is normative juridical to examine the problem of trademark infringement with normative research, and the material collection technique used is a literature study including laws, scientific articles, doctrines, etc. The study's results elaborated on the problem that, based on the legal sources collected, the naming of trusmi batik as a registered trademark is contrary to a general naming and a geographical indication naming. It was found that the trusmi batik artisan community has sought a form of protest against the naming of trusmi batik through trademarks in familial ways but has not met maximum results.